2021
DOI: 10.1038/s41598-021-91249-5
|View full text |Cite
|
Sign up to set email alerts
|

Flat hardness distribution in AA6061 joints by linear friction welding

Abstract: It is known that one of the main concerns associated with the conventional welding of precipitation-strengthened Al alloys is the formation of softening regions, resulting in the deterioration of mechanical properties. In this study, we show that linear friction welding (LFW) can completely suppress softening regions in precipitation-strengthened AA6061-T6 alloy by introducing a large shear strain and by controlling the interfacial temperature. We found that the LFW process resulted in an extremely low interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 30 publications
1
5
0
3
Order By: Relevance
“…The softening in Al joints can be suppressed by exploiting its rapid heating and cooling, a large introduced shear strain and a controlled temperature by optimum applied pressure [10][11][12]. Recently, it has been demonstrated that the high applied pressure is a promising method to perform LFW at a low temperature [13]. Furthermore, this process can increase productivity due to its extremely rapid process.…”
Section: Introductionmentioning
confidence: 99%
“…The softening in Al joints can be suppressed by exploiting its rapid heating and cooling, a large introduced shear strain and a controlled temperature by optimum applied pressure [10][11][12]. Recently, it has been demonstrated that the high applied pressure is a promising method to perform LFW at a low temperature [13]. Furthermore, this process can increase productivity due to its extremely rapid process.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 13 shows the maximum temperature during the welding processes measured using an infrared camera. As previous studied reported, [30][31][32][33][34][35] the welding temperature of both the Fe and Al sides was found to decrease with increasing applied pressure. On the other hand, the reduction in the welding temperature was relatively slight on the Al side, because of significant heat transfer from Fe side, which was elevated to a temperature above 1 000°C under all pressure conditions.…”
Section: Effect Of the Applied Pressurementioning
confidence: 57%
“…It can be seen from Figure 7 that the hardness of AA 5052 was only 85 HV [36], while the hardness of the anodic coating was 115 HV. After the anodic coating was treated by hydro-thermal technology, the hardness of the coating increased.…”
Section: Hardnessmentioning
confidence: 98%